The capacities of unstiffened T-stubs with thin plates and large bolts. (November 2021) - Özkılıç, Yasin Onuralp
Abstract: A comprehensive experimental study on unstiffened T-stubs was conducted in order to examine the effects of parameters influencing the capacities of the T-stubs. Pursuant to this goal, 35 unstiffened T-stubs were tested under monotonic loading up to failure, where significantly large deformations were observed. Flanges of T-stubs were selected from the thin plates of 6, 8 and 10 mm whereas bolts were selected as the large bolt of 27 mm. In this way, the capacity of T-stubs was governed by the bending capacity of flanges. Thickness of flange, width of flange, distance from a T-stub stem to bolt row, edge distance, bolt diameter and thickness of weld are selected as the parameters. The results showed that unstiffened T-stubs with thin plates and large bolts can exhibit significantly high ductility and capacity. Moreover, the results revealed that the design recommendations given by AISC 358-16 and EN1993-1-8 predict the capacities of T-stubs conservatively. The average ratios of the actual to predicted plastic capacity by AISC 358-16 and EC3:1-8 are 1.96 and 1.66 (1.34 for Method 2), respectively. These ratios modify to 8.36 and 7.14 (5.88 for Method 2) for the ultimate capacity. The source of the underestimation is attributed to the distance between the plastic hinges. A new yield line pattern is proposed to predict the plastic resistance more accurately. Moreover, an expression is developed to estimate the ultimate resistance. The averages of actual to predicted ratios of the proposed modifications are 1.05 and 1.03 for the plastic and ultimate capacities, respectively. Graphical abstract: Unlabelled Image Highlights: 35 experiments were conducted to investigate the capacity of T-stubs with thin plates and large bolts. AISC 358 and EC3 underestimated the capacities of unstiffened T-stubs. The underestimation can be attributed to the distance between the plastic hinges. A new yield line is developed to predict the plastic capacity of unstiffened T-stubs. An expression is proposed to estimate the ultimate capacity of unstiffened T-stubs.